RELICT SAPPHIRINE IN PYROPIC GARNET FROM THE EASTERN SØR RONDANE MOUNTAINS, ANTARCTICA - アサミ, マサオ; マキモト, ヒロシ /; ASAMI, Masao; MAKIMOTO, Hiroshi; GREW, Edward S. (National Institute of Polar Research, 1994)
P(論文) Sapphirine-bearing biotitic schist forms a reaction zone between an ultramafic lens and its host biotite-hornblende gneiss at Balchenfjella, which is underlain by migmatitic complex metamorphosed under granulite-facies conditions in the Late Proterozoic and under amphibolite-facies conditions in the Early Paleozoic. This schist consists of porphyroblastic garnet, the core of which is compositionally homogeneous pyrope-almandine (X_<Mg>=Mg/(Fe+Mg)≅0.50) surrounded by an almandine rim (X_<Mg>≅0.27), biotite (X_<Mg>=0.70-0.73), plagioclase (An_<75-87>), spinel (X_<Mg>=0.26-0.36), corundum, rutile and zircon. In addition, individual garnet porphyroblasts enclose different mineral associations in the magnesian cores as follows : (A) sapphirine (X_<Mg>=0.75-0.85), commonly with kyanite, and, locally, with spinel (X_<Mg>=0.50-0.68), (B) kyanite only, and (C) gedrite (X_<Mg>=0.75-0.78)+quartz aggregates. The mineral associations sapphirine+kyanite±spinel and gedrite+quartz±kyanite are inferred to be relict assemblages of the prograde P-T path, and the magnesian garnet cores to have been homogenized during the granulite-facies event. Differences in the associations are presumed to have resulted from pre-metamorphic chemical heterogeneity in the precursor to the biotitic schist. These mineral associations suggest a clockwise prograde P-T trajectory entirely within the kyanite field; the assemblage sapphirine+kyanite might have been stable as T approached 700℃ constraining P to be at least 8 kbar. Further increase in temperature was accompanied by a small decrease in P to the 7-8 kbar (at T=760-800℃) estimated for peak conditions in the granulite-facies by M. ASAMI et al. (Proc. NIPR Symp. Antarct. Geosci., 6,57,1993). The relict sapphirine-kyanite assemblages in the Sør Rondane Mountains are similar to those reported from the Luzow-Holm Bay complex, Antarctica, and the Highland Complex, Sri Lanka (e.g. Y. OGO et al. : Recent Progress in Antarctic Earth Science, ed. ...